Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.bbamem.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Aβ peptide creates lipid density depression in DMPC bilayer

Abstract: Using isobaric-isothermal replica exchange molecular dynamics and all-atom explicit water model we study the impact of Aβ monomer binding on the equilibrium properties of DMPC bilayer. We found that partial insertion of Aβ peptide into the bilayer reduces the density of lipids in the binding "footprint" and indents the bilayer thus creating a lipid density depression. Our simulations also reveal thinning of the bilayer and a decrease in the area per lipid in the proximity of Aβ. Although structural analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 43 publications
7
60
0
Order By: Relevance
“…The amino-truncated A β 10–40 monomer was chosen as a proxy to full-length A β 1–40. Our previous simulations 29,30 have indicated that this peptide reproduces several A β 1–40 experimental observations, including the distribution of helical structure along the sequence and partial insertion of A β in the bilayer 12,31,32 . Additionally, A β 10–40 peptides are naturally occurring cytotoxic and amyloidogenic species 3336 .…”
Section: Methodssupporting
confidence: 64%
See 4 more Smart Citations
“…The amino-truncated A β 10–40 monomer was chosen as a proxy to full-length A β 1–40. Our previous simulations 29,30 have indicated that this peptide reproduces several A β 1–40 experimental observations, including the distribution of helical structure along the sequence and partial insertion of A β in the bilayer 12,31,32 . Additionally, A β 10–40 peptides are naturally occurring cytotoxic and amyloidogenic species 3336 .…”
Section: Methodssupporting
confidence: 64%
“…The contribution of all restraints to the potential energy at 330 K is minor (≈0.6 kcal/mol RT ). Moreover, our previous studies have shown that the effect of restraints on lipid structural properties is generally within the sampling error 30,45 . Because we detected no instances of interpeptide interactions via amino acid side chain contacts or cross-bridges by a third molecule, we assume that the peptides bind to the bilayer independently as monomers.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations